As tecnologias da informação e da comunicação e o processo ensino-aprendizagem: nova paisagem, novas sensibilidades: uma abordagem levyniana - Silva, Neilton Costa da (2006)
The objective of this research is relating to appropriated forms of Technologies of the Information and Communication (T.I.C.) on the Scholar Teaching-Learning process and prepositions of Pierre Lévy about virtualization and the potentialities of the T.I.C., while conditioning tools of the processes which will give form to a social reality from the people in modern times. Its proposal is to investigate how the T.I.C. are being appropriated by students and professors, through identification of factors that will contribute to increase their common senses and scholar space meanings. The central question is: The T.I.C. are being appropriated as things , or however, being as technological artifacts to process and access registered historical containing, to calculate and do some jobs or, as objects mediators from the human competence, cherished materials, non territorial, potential helpers and re-coding readers on the scholar teaching-learning process, contributing all together to the development of new education practices? The area of observation chosen was the Federal Center of Technological Education of Sergipe, (CEFET-SE) in Brazil, especially the Courses of Electronics and Computing Science from this institution, where it was done a research in between two groups on the referred subjects, which permitted to collect the necessary information to conclude the final results presented in this research.